Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Keputusan Investasi Maysarakat di Daerah Kramat Jegu Sidoarjo - Ghoravira, Dextar Mahdi; Pujianto, Agung; Nasution, Ute Chairuz M. (Research Journal of Social Science and Economics, 2025)
This research aims to analyze the influence of financial literacy and financial inclusion on investment decisions of the community in the Kramat Jegu area, Sidoarjo. Financial literacy encompasses individuals’ knowledge, skills, and understanding of financial concepts, while financial inclusion focuses on broader access to formal financial services. Investment decisions involve the selection of investment instruments and allocation of funds to achieve long-term financial goals. Data were obtained through questionnaires distributed to respondents who are members of the community in the Kramat Jegu area, Sidoarjo. The analysis of data using the linear regression method indicates that financial literacy does not have a significant influence on the investment decisions of the community. This means that individuals’ financial literacy does not necessarily translate into a desire to make investment decisions. Additionally, financial inclusion also does not have a significant influence on investment decisions. Individuals with broader access to formal financial services do not necessarily make better investment decisions.The findings suggest the need to enhance financial literacy through educational programs, training, and campaigns targeting the community in the area. Efforts to expand access to formal financial services, such as banks and other financial institutions, should also be undertaken to enable individuals to make better investment decisions. This research contributes to understanding the relationship between financial literacy, financial inclusion, and investment decisions of the community in the Kramat Jegu area, Sidoarjo. The results of this study can serve as a reference for the government, financial institutions, and relevant organizations in designing and implementing programs that aim to improve financial literacy and financial inclusion in the area. Ultimately, these efforts can help individuals make better investment decisions and enhance their financial well-being.